PENINGKATAN NILAI EKONOMI JAGUNG DENGAN DIVERSIFKASI OLAHAN PANGAN BERBASIS KEARIFAN LOKAL DIKABUPATEN NGADA - Victoria Ayu Puspita; Umbu Awang Hamakonda; Polikarpus Oba (Jurnal Agriovet, 2024)
East Nusa Tenggara Province, especially Ngada Regency, continues to intensively develop corn production, reaching 21,062 tonnes and is recorded as contributing 3.01% of corn production in NTT Province. The potential of processed corn has not been utilized optimally in product diversification due to the lack of knowledge regarding the nutritional content of corn compared to rice. Processed food products made from corn based on local wisdom in this research are corn rice, bose corn and uta tabha. The aim of this research is to analyze the added value of processed corn products, analyze the financial feasibility of corn processing businesses, namely income and R/C ratio. The research location was determined purposively by considering certain things. This research method is a quantitative method with a descriptive approach. The analysis method in this research is the Hayami method of added value analysis, income analysis and comparative analysis between Revenue and Cost followed by an explanation of each analysis result. The research results show that the corn-based food product that has the highest added value and R/C ratio is corn rice with an added value ratioof 47.2% and an R/C ratio of 2.57. So it can be recommended to use corn as a processed corn rice product to reduce dependence on rice which has experienced a significant price increase.